»Tarvelige« kirker til jævne folk: Den københavnske Kirkesag og Valdemar Kochs kirker - Koch, Lene (Kirkehistoriske Samlinger, 2022)
I forbindelse med Københavns voldsomme befolkningsstigning i slutningen af 1800-tallet blev kirkebyggeri et politisk stridspunkt. Københavns Kirkefond lod en række nye kirker bygge, baseret på private indsamlinger blandt frivillige bidragydere. Fondet anså nye små kirker som et vigtigt virkemiddel i arbejdet for at redde »de vantro masser« fra socialisme og fritænkeri. Artiklen fokuserer på arkitekten Valdemar Kochs overvejelser om, hvorledes man kunne sikre de fattige for kristendommen ved hjælp af kirkernes arkitektoniske og kunstneriske udtryksformer. Med Kapernaumskirken som case illustreres, hvorledes det hyggelige hjem bliver en model for kirkerummets indretning og udsmykning. Koch designede sine »tarvelige« småkirker i en ydmyg og egalitær stil. Hans skønvirke-prægede blomstermotiver var direkte inspireret af samtidigt japansk og britisk kunsthåndværk og sigtede mod at påvirke de fattige til aktiv deltagelse i deres menigheder. Summary As the Danish Capital of Copenhagen experienced a dramatic population expansion in the second half of the 19th century, the building of new churches became an urgent issue. As the old fortification area surrounding the city was opened for new settlement, no one seemed to think of building churches. As a result, the newly immigrated proletariat was left without proper access to ecclesiastical service at christenings, weddings, and funerals. By clever exploitation of this misconduct, charitable organizations, first of all The Copenhagen Church Building Society (Kirkefondet), succeeded in collecting private money to erect 19 churches between 1860 and 1910. Theologically, The Copenhagen Church Building Society was closely associated with the Inner Mission, an evangelical movement critical of the established church and dedicated to building more activist congregations among the new settlers. A means to reach this aim was to build small and modest churches for the poor. The Danish architect Valdemar Koch (1852-1902) became the architectural advisor of The Church Building Society (Kirkefondet) and built five out of the 19 new churches. He wrote extensively on the esthetic and architectural aspects of the building activities and was the architect of the foundation’s first permanent church, The Kapernaum church north-west of Copenhagen. The article focuses on the architectural expression of the churches and examines how the small new churches were built to accommodate the needs of the new parishioners. Not only as Sunday churches, but as »cosy [hyggelige] homes« to attract and win for Christianity an immigrant population, left to live under miserable conditions in tenement houses erected on the newly accessible grounds outside the city without proper public regulation. For this purpose, it was believed, small intimate churches decorated with »honest« art would be the best way to wring the individual away from the mass and establish a close relationship between the individual and the church. In this way the small churches were »modern« as they related constructively to a problem created by modernity by means of their historicist architectural expression. Using the Kapernaum Church as a case study, the article demonstrates how the »hyggelige« – cosy – small church was conceived as an educational and civilizing force in creating a new congregation. The architectural and decorative style used by Koch was historicism, an eclectic piecing together of various styles, roman, classical, and Renaissance elements, but consciously designed as non-monumental and egalitarian. The unique nature-motives of his church interiors were directly inspired by contemporary Japanese and British art. But whereas the British Arts and Crafts movement had a socialist orientation, Koch used his decorative style to lead the proletariat towards a Christian existence within the established society.